Antibacterial Activity of Guava Leaf Extract on The Growth of Aeromonas Hydrophila - Emmy Syafitri; Denni Kurniawan; Dwi Tika Afriani (Quagga: Jurnal Pendidikan dan Biologi, 2023)
Research on the benefits of guava leaves has been widely carried out because of their ability as an antibacterial and antifungal agent, especially in aquaculture. This study aims to determine the antibacterial activity of guava leaf extract against the growth of the pathogenic bacteria Aeromonas hydrophila in vitro. The method used to determine the antibacterial activity of guava leaf extract is the disc diffusion method. The activity test used a completely randomized design (CRD) consisting of 4 treatments with concentrations of guava leaf extract, namely 30%, 50%, 100%, and aqua dest as a control. Guava leaf extract was dissolved using 96% ethanol by the maceration method. Each treatment concentration was tested for its inhibitory power by calculating the apparent zone diameter that appeared against Aeromonas hydrophila bacteria. The data obtained were analyzed using analysis of variance with a 95% confidence level and, if significantly different, continued with the LSD test. The in vitro antibacterial activity test showed that guava leaf extract had a very significant effect on the growth of Aeromonas hydrophila bacteria (p<0.01) with a concentration of 50%, resulting in the most effective inhibition Aeromonas hydrophilla bacteria growth with a clear zone formed 18.33 mm. Based on the study results, it can be concluded that in vitro guava leaf extract with a concentration of 50% can inhibit the growth of Aeromonas hydrophila bacteria with the most significant clear zone yield.